Contemporary Art Museums and Youth: An Imperfect Genealogy of the Whitney Museum of American Art, New Museum, Tate and Whitechapel Gallery programmes - Silva, Carolina (Museum and Society, 2025)
The unique feature of the youth groups formed in contemporary art museums is the wider ecology to which they are connected, meaning simultaneously the idiosyncrasies of each institution and their educational programmes, the people who plan and facilitate those initiatives, and the private or public funding schemes in the background that make them possible. In this paper I present the genealogies of the youth programmes of four contemporary art museums – two located in New York, USA: the Whitney Museum of American Art and New Museum, and two in London, UK: Tate, and Whitechapel Gallery. Together they make the intricacies, tensions, and potentialities of long-term programmes for youth in museums visible, while challenging the linearity of historical narratives and opening directions for the future.